Socio-educational home environment in relation to students mathematics achievements - Jolita Dudaitė (Lietuvos Matematikos Rinkinys)
The article deals with impact of socio-educational home environment on Lithuanian Grade 8 students' mathematics achievements. Data of the Trends in International Mathematics and Science Study (TIMSS) is used for analysis. The results show high correlation between Lithuanian Grade 8 students' mathematics achievements and home-related factors. The higher relation is seen between mathematics achievements and educational home environment than between mathematics achievements and economical home environment.